(untitled) - Thomson, J. M. (Harmondsworth, 1974)
For some years, books in the field of transportation economics have, with few exceptions, followed a traditional pattern of devoting a substantial share of the text material to an intensive discussion of the historical and regulatory aspects of the industry. Likewise, considerable space is devoted to a description of the institutional aspects of the modes. This book does not depart from that time tested pattern in essence, but does contain what the author fondly hopes are some fundamental modifications of that basic framework. A significant share of the text is devoted to the macro-economic and micro-economic aspects of the industry. Further, the economic analysis is not isolated in a portion of the book, but an effort has been made to interlace it into all areas of the text and especially to focus the application of regulatory controls against the background of the economic character of the industry and the structure of the modern economy.
Keywords: Vận tải,Transportation